Plantar wart / Callus-corn. - Pisani, V. (European Journal of Pediatric Dermatology, 2015)
Plantar warts and calluses are both characterized by increased thickness of the horny layer. The plantar wart is painful. However, also the callus can be painful when inside there is a corn; the latter is a circumscribed hyperkeratosis sized as a lentil overlying a bony protrusion (it is usually localized on the dorsal surface of the 2nd and 5th toe or in the interdigital space of the foot, especially the 4th).